Methods of Nursing Shift Handover and Their Outcome in Terms of Patient Safety in Healthcare Systems: A Systematic Review - Verma, Ranjana; Phalswal, Uma; Kalal, Nipin; Shafqat, Naseema; Verma, Mamta; Sharma, Suresh; Das, Saikat; Agrawal, Amit (National Journal of Community Medicine, 2025)
Introduction: Patient handover is a critical component of healthcare delivery and directly influences patient safety and quality of care. Incomplete or inaccurate handovers increase the risk of errors and disrupt continuity. This review examines current handover practices and their implications for healthcare quality and safety. Methods: A systematic review was conducted following PRISMA guidelines. Scopus, ScienceDirect, PubMed, and Cochrane were searched using terms related to nursing and clinical shift handover, patient safety, quality improvement, and patient care. Eligible studies included qualitative, quasi-experimental, and cross-sectional designs that met predefined criteria. Methodological quality was assessed using the JBI appraisal tool. Results: Of 570 records identified, 11 studies met the inclusion criteria and were analyzed. The findings indicated that the absence of standard operating protocols resulted in poor communication, inadequate coordination, ineffective time management, and organizational deficiencies. Communication failure was the most consistently reported challenge affecting handover efficiency and patient safety. Conclusion: Variation exists in the consistency and completeness of information exchanged during shift handovers. Development and implementation of structured guidelines for shift reporting are recommended to improve reliability and continuity of care. These guidelines should facilitate systematic information transfer and handling of patient data. Accessible SOPs at the point of care may support safer and efficient handover practices.